Prevalence of vitamin D deficiency and its association with adverse obstetric outcomes among pregnant women in Uganda: a cross-sectional study - Cristina Reverzani; Daniel Zaake; Faridah Nansubuga; Herman Ssempewo; Leonard Manirakiza; Anthony Kayiira; Gilbert Tumwine (BMJ Open)
Objective There is a dearth of published data on the vitamin D status of the Ugandan population; the objective of the study was to determine the prevalence of vitamin D deficiency among pregnant women in Uganda and its associations with maternal characteristics and adverse foetal-maternal outcomes.Study design and setting We conducted a cross-sectional study on pregnant women admitted to a tertiary referral hospital in Kampala, Uganda for delivery during the study period from July to December 2023.Participants The study was conducted on 351 pregnant women aged ≥18 years who consented to participate in the study, who had a single intrauterine pregnancy and a gestational age greater than 26 weeks, and who delivered at St. Francis Hospital, Nsambya. We excluded pregnant women admitted to the hospital longer than 1 week before delivery; pregnant women with self-reported pre-existing kidney diseases, liver diseases, or gut or malabsorption disorders and pregnant women with severe pregnancy-unrelated comorbidities requiring intensive care unit admission before delivery.Interventions Maternal venous blood was collected at admission, and serum 25-hydroxy-vitamin D (25(OH)D) was measured by an electrochemiluminescence binding assay.Primary and secondary outcome measures Maternal sociodemographic characteristics and obstetric-medical factors, and adverse maternal and foetal outcomes were captured by using a data collection form. The data were analysed by logistic regression analysis at the univariate, bivariate and multivariate levels.Results The prevalence of vitamin D deficiency, defined as a serum 25(OH)D concentration less than 20 ng/mL, was 40.2%. This was seen more among the Muslims (OR 2.4, 95% CI 1.33 to 4.43, p value 0.004), members of the Banyankore tribe (OR 2.1, 95% CI 1.02 to 4.36, p value 0.043) and primigravidae (OR 0.6 for women with parity of 1–4 compared with primigravidity, 95% CI 0.36 to 0.94, p value 0.028). Among adverse maternal outcomes, vitamin D deficiency was associated with hypertensive disorders in pregnancy (OR 2.4, 95% CI 1.16 to 4.10, p value <0.001), in particular gestational hypertension (OR 2.2, 95% CI 1.21 to 4.94, p value 0.014), and pre-eclampsia/eclampsia/haemolysis, elevated liver enzymes and low platelets syndrome (OR 2.9, 95% CI 1.45 to 6.08, p value 0.003), with increased preterm birth (OR of 4.0, 95% CI 1.78 to 10.84, p value<0.001) and with delivery of babies with low birth weight (OR 4.2, 95% CI 2.63 to 13.62, p value 0.001).Conclusions The study found a high prevalence (40.2%) of vitamin D deficiency among pregnant women delivering at St. Francis Hospital, Nsambya. Additionally, vitamin D deficiency was linked with adverse maternal and foetal outcomes such as hypertensive disorders in pregnancy, preterm birth and low birth weight.